Idiopathic spontaneous hemoperitoneum in pregnancy: a rare entity - Rai, Geeta Katheit; Aggarwal, Niharika; Vidyasagar, Veena; Kaul, Sanjeevani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Spontaneous hemoperitoneum in pregnancy (SHiP) is a very rare occurrence and is defined as sudden non-traumatic intraperitoneal bleeding in pregnancy and up to 42 days postpartum. The incidence is currently extremely difficult to estimate due to the lack of worldwide surveillance. We present a case of a 32-year-old G4P2L2A1 at 38 weeks of gestation. The patient was referred from a private hospital in a state of shock. The patient had a history of abdominal pain followed by fainting attack. The patient underwent laparotomy in view of suspected uterine rupture. Intraoperatively there was hemoperitoneum of unknown origin. The maternal and fetal outcome was poor in this case. In literature there are only very few reported cases of spontaneous hemoperitoneum in pregnancy.